Ofício do magistrado do distrito de Xiangshan, Yang, ao procurador de Macau, sobre a compra de rapé (1777)
This is a Qing dynasty imperial edict, dated the 1st day of the seventh month in the 42nd year of the Qianlong reign (1777 CE), issued by His Honour Magistrate Yang and bearing seals of the Imperial Maritime Customs Service, Inspector-General’s Office, and a *jiājiǎng* (Commendation) seal. The document addresses Indigenous Headmen—including Vileto—and Macau Customs Authorities, concerning the seizure and official requisition of opium imported by foreign vessels arriving at the port, totalling over fifty *lā* (c. 62.5 kg) and four *tǒng* (c. 160–200 kg). It records repeated demands for surrender of this contraband, condemns foreign merchants’ disregard of directives and engagement in unauthorised private trade prior to tributary approval, and mandates repackaging of specified quantities into standard bottles for tribute ceremony use. Marginalia include dating references to the Xiá era (a non-standard designation possibly indicating scribal error or alternative calendrical notation), archival identifiers (T54, 1477, T5 *zi*), and an urgent annotation (*jí*). The text reflects administrative procedures governing maritime trade, opium regulation, tributary protocol, and inter-ethnic governance in late eighteenth-century southern China, particularly in relation to Macau and Indigenous communities under Qing jurisdiction.
Keywords: Foreign Vessel Regulation; Imperial Maritime Customs Service; Indigenous Headmen; Jiājiǎng Seal; Macau Customs Authorities; Opium Requisition; Qianlong reign; Qing Dynasty Imperial Edict; Qing Tributary Protocol; Transcription